Oficinas pedagógicas para comunicação intergeracional entre idosos e jovens - Barros, Kilma Cunha de (2019)
Introduction: Population aging occurs around the world and brings with it some concerns for causing social and biological consequences for society. Studies show that intergenerational communication between the elderly young people favors the construction of bonds, undoes barriers to stereotypes, social and cultural prejudices.Objectives: To establish intergenerational communicationbetweenthe elderly and young people through educational workshops.Method: This is a descriptive study with qualitative approach, which used the methodology of proplematization as a pedagogical option. In the first stage of the research, an integrative review was carried out and in the second stage, five pedagogical workshops were built and applied based on the problematization methodology with 18 elderly and 18 young people. In the investigation data, similarity analysis and word cloud were used through Iramuteq. The results show that intervention activities through pedagogical workshops cause changes in perception in the elderly and young people and promote intergenerational communication between this specific group. Therefore, it is possible to conclude that the pedagogical workshops bring in their framework the necessary structure as a means that enhances and promotes intergenerational communicatin between the elderly and young people. It is also suggested that this of workshop, contemplates other generations and occurs at different times as an educational intervention activity in professional training courses in the health area. Therefore, as a product of the dissertation, an orientation plan for the construction of pedagogical workshops in the face of intergenerational communication was built.